2019
DOI: 10.1024/0301-1526/a000774
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of anticoagulation therapy following endovascular thrombus removal and stent placement for acute iliofemoral deep vein thrombosis

Abstract: Summary. Background: The optimal duration of anticoagulation therapy (AT) following catheter-based therapy of acute iliofemoral deep vein thrombosis (IFDVT) with stent placement is unknown. Theoretically, resolving the underlying obstructive iliac vein lesion by a stent may eliminate the main trigger for recurrence, the post-thrombotic syndrome (PTS), and the need for extended-duration AT. Patients and methods: From 113 patients with acute IFDVT who underwent endovascular thrombus removal and stent placement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Compared with data on VTE recurrence rates in patients with acute iliofemoral DVT who underwent thrombus removal and venous stent placement, we observed an almost twofold increased VTE recurrence rate in PTS patients (7.1 vs. 13.0 events per 100 patient-years). 25,26 A possible explanation for this observation is that acute iliofemoral DVT patients often have preserved femoral leg inflow veins, and less often require stents below the inguinal ligament. For patients with PTS, the use of antiplatelet agents in addition to anticoagulants appears plausible to address the risk of ST in the first 6 months after stent recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with data on VTE recurrence rates in patients with acute iliofemoral DVT who underwent thrombus removal and venous stent placement, we observed an almost twofold increased VTE recurrence rate in PTS patients (7.1 vs. 13.0 events per 100 patient-years). 25,26 A possible explanation for this observation is that acute iliofemoral DVT patients often have preserved femoral leg inflow veins, and less often require stents below the inguinal ligament. For patients with PTS, the use of antiplatelet agents in addition to anticoagulants appears plausible to address the risk of ST in the first 6 months after stent recanalization.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless it has been reported that in selected patients with acute iliofemoral deep vein thrombosis and patent venous stent, particularly younger and otherwise healthy patients with May-Thurner syndrome, anticoagulation therapy can be safely discontinued 3 to 12 months after endovascular treatment. 7 Our patient received anticoagulation for 1 year after surgery.…”
Section: Discussionmentioning
confidence: 89%
“…Control group/Comparison group Follow-up PTS no difference in patency and clinical outcome after 3-12 months vs longer duration with AC in stented patients after CDT, as well as no difference between vitamin K-antagonists and rivaroxaban for the first 3 months period of treatment (41,42). Many reviews have been published.…”
Section: Thrombus Removal Typementioning
confidence: 99%